RANCANG BANGUN SISTEM INFORMASI INVENTORY BERBASIS WEB PADA TOKO GALERY FASHION - Ema Dwi Septiana; Dwi Hartanti; MOH MUHTAROM (Jurnal DutaCom, 2023)
Abstract— The Galery Fashion store is a shop engaged in the Muslimah fashion sector that sells several types of products such as tunics, midi dresses, blouses and robes online. Media used in selling products by utilizing various marketplaces such as Lazada, Shopee, Tiktok, and Tokopedia. Stock management is carried out at the Fashion Galery Store still semi-computerized using Ms.Excel. In this way it makes work less effective and efficient. To improve performance so that it is more optimal, the Fashion Gallery Store requires a system that can assist in managing inventory data. The purpose of this research is to build a web-based inventory information system that is able to facilitate and efficiently each job and process of managing stock items at the store. The development method used is the waterfall method as a system development method. The waterfall method is a method that provides a sequential or step-by-step software life cycle approach starting from analysis, design, coding, testing, and maintenance. The programming language used by the author is PHP and MySQL as the database. The result of this research is that the inventory information system makes stock management at the Fashion Galery Store easier, more effective and efficient. The results of this study are a web-based inventory information system that can facilitate the process of managing stock items and making stock reports. The results of Blackbox testing of this system yield a calculation result of 98.33% which states that this application can be run according to user needs and the results show that the system is running as expected and is feasible to implement. Keywords— Stock Goods, Waterfall, PHP, MySQL, Website.